ANALISIS MANAJEMEN RISIKO PENGGUNAAN APLIKASI GOJEK DENGAN METODE FAILURE MODE AND EFFECTS ANALYSIS (FMEA) - Brigityana, Nurvi; Dhiya’ulhaq, Khansa Yumna; Suryadi, Leinia; Ningtyas, Mastuty Ayu (JURNAL MANAJEMEN RISIKO, 2024)
In the continuously evolving digital era, technology-based applications like Gojek have become an integral part of daily life. While offering numerous conveniences, the use of these applications also entails various risks for both users and service providers. Therefore, this study aims to identify these risks using the Failure Mode and Effects Analysis (FMEA) method, which helps in identifying, analyzing, and mitigating potential risks. This research employs a quantitative method with a survey approach involving a random sample of Gojek users. Data were collected through questionnaires assessing the three main FMEA parameters: Severity, Occurrence, and Detection. Risk analysis was conducted on three asset categories: Information/Data, Software, and People. Each risk was then analyzed to determine the Risk Priority Number (RPN), indicating the priority of risk management based on its potential impact. The study results show that data leakage from merchant partners and discrepancies in Gofood orders are the highest RPN risks requiring immediate attention. By identifying and assessing these risks, it is hoped that Gojek can take appropriate mitigation steps to enhance security and user satisfaction.